Build a Service Excellence Culture of Pleasure to Customers - Tanti Widia Nurdiani; R.M Mahrus Alie (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
Customer service is an important aspect for most businesses in retaining customers, maintaining high revenues and acquiring new customers. The purpose of this study is to examine the aspects that need to be built in superior cultural services to customers. The theories used are customer-oriented culture, staff management and customer retention. In this qualitative research, descriptive analytic method is used to collect data and analyze and interpret the results. The findings show which aspects and dimensions of service quality are significant in building a vision of total service quality, different country cultures. Customer trust affects repurchase intentions and word of mouth promotion. The more trust a customer has in a company, the more likely he is to recommend it to others.